NAVIGATING THE COMPLEXITY: FORENSIC ANALYSIS OF LIKELIHOOD OF CONFUSION IN PAKISTANI LOCAL TRADEMARKS - Sumayia Tanveer; Zubia Shakeel; Muhammad Farukh Arslan (International Journal of Contemporary Issues in Social Sciences, 2024)
This study examined the impact of phonetic similarities and grapheme-level features on consumer confusion over local trademarks in Pakistan. By using a descriptive qualitative research design, the analysis focuses on six trademark to investigate the level of confusion these linguistic aspects create. The theoretical framework which is used in this research was Shuy’s (2002) linguistic techniques. The results highlight that identical graphemes significantly increase the likelihood of customer misinterpretation. Similarly, phonetic resemblance can give rise to misunderstandings, particularly in terms of syllable structures and stress patterns. These findings demonstrate that how significant it is for trademark owners to employ distinct grapheme patterns and phonetic intelligibility in order to ensure brand identification and prevent confusion. By highlighting specific linguistics aspects that lead to consumer misunderstanding and providing advice for making legal decisions in trademark conflict, the study contributes to the fields of forensic linguistics and trademark law. Further study in this area may lead to better consumer protection strategies and trademark design processes.